PENGARUH DANA PIHAK KETIGA PERBANKAN SYARIAH TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA: A Theoritical Approach - Sari, Imelda; Suparno, Suparno (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2024)
Economic growth is an important determinant of individual income levels and the growth rate of a particular region, measured through GDP. The NPF ratio serves as a metric to assess credit quality or the bank's competence in managing credit risk. DPK includes funds obtained from the public in the form of investment products. The methods used in this article include a qualitative approach involving a literature study or library-based research. The purpose of this investigation involves analyzing the prevailing theories through a comparative examination of the literature pertaining to the research results. The literature used in this study includes research findings and reviews derived from nationally recognized scholarly articles in accordance with financial management. All articles used in this study were sourced from the electronic data search engines ResearchGate and Google Scholar. Through the analysis of the determinants of Islamic banking (NPF and DPK), a significant correlation was identified. The impact of NPF on economic growth manifests in its capacity to increase borrowers' ability to repay loans, while simultaneously incurring an escalation of loan risk. Similarly, the effect of Third Party Funds on economic growth is illustrated by the important role that economic growth plays in the capitalization of Islamic banks, consequently exerting a major influence on the size of third party funds attracted by Islamic banks. Based on the aforementioned findings, it is highly recommended that researchers proceed to conduct a comprehensive literature review to explore additional independent variables (such as Return on Assets and Capital Adequacy Ratio) that impact economic growth during the Covid-19 pandemic.